2023
DOI: 10.3390/ijms241915001
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Endometriosis: Insights into Inflammation and Progesterone Resistance

Jing-Xian Hon,
Norhazlina Abdul Wahab,
Abdul Kadir Abdul Karim
et al.

Abstract: Endometriosis, a non-malignant gynecological disorder influenced by estrogen, involves the growth of endometrial tissue outside the uterus. Its development includes processes such as inflammation, progesterone resistance, angiogenesis, and cell proliferation. Epigenetic factors, particularly the dysregulation of microRNAs (miRNAs), have emerged as key factors in these mechanisms in endometriosis. This review aims to unveil the intricate molecular processes that control inflammation, progesterone resistance, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…Results of several studies remain controversial and even contradictory due to the irreproducible nature of the studies ( 12 , 100 ). At present, no single or groups of miRNA biomarkers has sufficient specificity and sensitivity in the diagnosis of EM ( 101 ).…”
Section: New Non-invasive Biomarkers In Emmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of several studies remain controversial and even contradictory due to the irreproducible nature of the studies ( 12 , 100 ). At present, no single or groups of miRNA biomarkers has sufficient specificity and sensitivity in the diagnosis of EM ( 101 ).…”
Section: New Non-invasive Biomarkers In Emmentioning
confidence: 99%
“…This indicates that angiogenesis is a key link in the pathogenesis of EM, which represents a potential target for development of future diagnostic and therapeutic strategies. Recent study of angiogenic mechanisms in EM has revealed the importance and potential role of angiogenesis-related pathways and markers of EM for diagnosis and treatment ( 9 12 ). That has provided a new direction for the discovery of novel targets of anti-angiogenic action and therapy and novel lines of thought and strategies for clinical treatment of EM.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating gene expression in embryo implantation, endometriosis and ovarian cancer [10,40,41,63] have all found altered expression of LIF, and other genetic and epigenetic changes, such as CD44 and miR 99a-5p [42,43], supporting our hypothesis that the uterine secretome is important in all these processes. miRNA which has been reported in both endometriosis and uterine secretory exosomes, such as miR-302a and let-7b-5p are examples of epigenetic changes [64,65] that will be further investigated. EM has been shown to have elevated LIF in the peritoneal fluid [9,10].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, a significant role of stem cell-based dysfunction in the formation of initial endometrial lesions is suspected. There is increasing evidence that the role of epigenetic mechanisms and processes in endometriosis has been underestimated [5,[10][11][12]. This conclusion is based on the fact that heritable phenotype changes that do not interfere with the DNA sequence are common triggers for hormonal, immunological, and inflammatory disorders, which play a key role in the formation of endometriotic foci [7].…”
mentioning
confidence: 99%